Hearing spiritually significant voices: A phenomenological survey and taxonomy. Issue 3 (7th December 2020) - Cook, Christopher C H; Powell, Adam; Alderson-Day, Ben; Woods, Angela
Abstract : Whereas previous research in the medical humanities has tended to neglect theology and religious studies, these disciplines sometimes have a very important contribution to make. The hearing of spiritually significant voices provides a case in point. The context, content and identity of these voices, all of which have typically not been seen as important in the assessment of auditory–verbal hallucinations (AVHs) within psychiatry, are key to understanding their spiritual significance. A taxonomy of spiritually significant voices is proposed, which takes into account frequency, context, affect and identity of the voice. In a predominantly Christian sample of 58 people who reported having heard spiritually significant voices, most began in adult life and were infrequent experiences. Almost 90% reported that the voice was divine in identity and approximately one-third were heard in the context of prayer. The phenomenological characteristics of these voices were different from those in previous studies of voice hearing (AVHs). Most comprised a single voice; half were auditory; and a quarter were more thought-like (the rest being a mixture). Only half were characterful, and one-third included commands or prompts. The voices were experienced positively and as meaningful. The survey has implications for both clinical and pastoral work. The phenomenology of spiritually significant voices may be confused with that of psychopathology, thus potentially leading to misdiagnosis of normal religious experiences. The finding of meaning in content and context may be important in voice hearing more widely, and especially in coping with negative or distressing voices.